Neonatal septicemia- a smooth technique of diagnosis in developing countries - N. S., Nayana; N., Sreenivas (International Journal of Research in Medical Sciences, 2017)
Background: Neonatal septicemia is characterized by clinical signs and symptoms accompanied by bacteremia in the first month of life. As per National Neonatal Perinatal Database (NNPD) 2002-2003, the incidence of neonatal sepsis in India was 30 per 1000 live birth. C-reactive protein (CRP), an acute phase reactant has advantages of low serum levels in normal infants, a rapid rise after 12 to 24 hours of sepsis and a massive rise thereafter as long as inflammatory stimuli persist and followed by immediate fall of serum level as soon as inflammation subside. Methods: Total 100 cases were studied at NICU, K.R Hospital, Mysore, India. Peripheral blood smear was prepared by heel prick and were stained using Leishman stain. Total leucocyte count was performed by using automated haematology analyzer. I/T (immature to total neutrophil) ratio were calculated by dividing the total immature count by total neutrophil count (including both mature and immature neutrophil count. C reactive protein was assessed by kit using CRP Latex, agglutination slide test. For Micro ESR blood was collected in preheparinised microhematocrit tubes of 75 mm length with an internal diameter of 1.1 mm & external diameter of 1.5 mm by heel prick technique. Results: Our study revealed that, among 100 children under study, males of low birth weight were commonly affected. Among the investigations I:T ratio and CRP shows a better sensitivity and specificity for early diagnosis of neonatal sepsis. Conclusions: Amongst all the hematological parameters Immature to total neutrophil (I:T) ratio has a reasonably good predictive value for early diagnosis of neonatal septicemia. This study is done as an endeavor to add to something about our preexisting knowledge of diagnosis of neonatal sepsis early for better management of this group of patients especially in developing countries.